Association between the length of stay in rehabilitation and mortality among the adults with Parkinson’s disease: 2009–2019 Korean National Health Insurance Service Databases - Bae, Suyeong; Hong, Ickpyo; Baek, Min Seok (Frontiers in Aging Neuroscience, 2024)
Background: Rehabilitation is recognized as an effective means of alleviating the symptoms of Parkinson's disease (PD) and improving the physical and cognitive functions of patients with PD. However, research often focuses on short-term outcomes such as functioning and quality of life. This study investigated the association between the length of stay in rehabilitation and mortality among patients with PD.Methods: Using the Korean National Health Insurance Service database, we identified 636 participants diagnosed with PD who received rehabilitation. The main outcome was all-cause mortality. We used a Cox proportional hazards regression model to examine the relationship between length of stay in rehabilitation and mortality among patients with PD.The final sample comprised 374 females (58.81%) and 262 males (41.19%). A survival analysis revealed a significant association between the length of stay in rehabilitation and mortality, with a decrease in mortality of 16.1% in patients with PD who received one year of rehabilitation (hazard ratio = 0.839, 95% confidence interval = 0.788-0.895).Our findings underscore the potential benefits of timely implementation of rehabilitative interventions in patients with PD and the need for comprehensive and long-term rehabilitation strategies. It also highlights the necessity of such services for patients with PD and the importance of developing patient-centered rehabilitation guidelines.